Normocomplementaemic Urticarial Vasculitis in a 19-Month-Old Girl - Peter Williams (Case Reports in Pediatrics)
Urticaria is common in children. Urticarial vasculitis (UV) is a potentially more serious, rare variant. The youngest reported case was 12 months of age. A systemically well, 19-month-old girl presented with her mother who was concerned about the development of a rash. On presentation, the child had normal vital signs, was alert, and was well and playing with toys. There was a widespread urticarial rash (raised, pruritic, and erythematous) that was most apparent on the trunk with minimal rash on the legs. Overlying this urticarial rash in a similar distribution was a blotchy, palpable purpuric rash and associated hyperpigmentation. Investigations revealed a normal level of haemoglobin, white cells, platelets, and electrolytes. Renal function, international normalised ratio, and activated partial thromboplastin time were all normal. There was no blood or protein in the urine. The erythrocyte sedimentation rate was mildly elevated at 19 mm/hour. Complement results (including C1q) obtained later were normal. This case is striking not only because of the rarity of UV in children but also due to the unique diagnostic and prognostic challenges that it raises.